Comparison of recovery patterns of gait patterns according to the paralyzed side in Korean stroke patients: Protocol for a retrospective chart review. Issue 35 (August 2018) - Kim, Cheol-Hyun; Chu, Hongmin; Park, Chanran; Kang, Geon-hui; Seo, Jihye; Sung, Kang-keyng; Lee, Sangkwan
Abstract: Introduction: In Traditional Korean Medicine (TKM), diseases on the left or right side of the human body have been treated differently according to the theory of Donguibogam, which is an encyclopedic source for TKM. In the Wind chapter of Donguibogam, left hemiparesis due to stroke is called Tan, a sort of Hyeol-Byeong, and right hemiparesis due to stroke is called Tan, a sort of Gi-Byeong. As neuroscience develops, it has been shown that the functions of the left and right hemispheres differ, as do the symptoms caused by differently located lesions in the brain. In light of these recent findings and the theory of Donguibogam, it may be useful when treating patients in clinical practice to consider the side of the human body on which symptoms appear. The aim here is to establish whether side-dependent treatments are more effective in treating patients with symptoms on different sides of the body. Specifically, this exploratory study investigates changes in gait pattern among stroke patients with hemiparesis or hemiplegia during gait recovery. Methods: To develop this protocol, a retrospective review of charts will be used to assess differences in gait recovery patterns among stroke patients with left or right hemiparesis, using gait analysis systems that include GAITRite, G-walk, and Treadmill. The data will be selected from gait analysis performed more than twice in the period from September 1, 2017 to June 31, 2018 at Wonkwang University Gwangju Hospital (WKUGH). Results: The primary outcomes include spatiotemporal parameters obtained using GAITRite (FAP, velocity, step length, swing time, and stance time); symmetric parameters obtained using G-walk (tilt, obliquity, and pelvis rotation symmetry); and center of pressure (COP) area and velocity as measured by Treadmill. Discussion: This will be the first study to analyze the gait recovery pattern of stroke patients according to the paralyzed side by comparing spatiotemporal, symmetric, and COP parameters using gait analysis systems. Like all retrospective studies, the present research was subject to certain limitations related to bias (selection bias, recall bias, misclassification bias, confounding value bias), difficulty in assessing temporal relationships, and small sample size. However, these limitations were of less significance here because gait parameters and body side of symptoms of hemiplegia or hemiparesis are relatively clear. Conclusion: If the use of gait analysis systems (GAITRite, G-walk, and Treadmill) confirms differences in gait recovery pattern among stroke patients according to the paralyzed side, the findings will provide essential evidence for differential treatment of stroke patients on that basis.